Evaluation of rutting resistance and geotechnical properties of cement stabilized recycled glass, brick and concrete triple blends. (May 2022) - Senanayake, Muditha; Arulrajah, Arul; Maghool, Farshid; Horpibulsuk, Suksun
Abstract: Recycled glass, construction and demolition (C&D) wastes are increasingly being used as sustainable materials in road construction works. Recycled materials are a fit-for-purpose replacement for limited supplies of virgin quarried materials particularly in pavement construction works. The main objective of this research was to assess the performance of cement stabilized recycled glass (RG), crushed brick (CB) and recycled concrete aggregate (RCA) in triple blends while also maximizing the RG percentages in base and subbase pavement applications. Seven recycled material triple blends comprising 0%, 15%, 20%, 25%, 30%, 35%, 40% of RG incorporated with 20% CB and varying percentages of RCA up to 80% with 3% cement were evaluated in this research. The laboratory assessment comprised particle size distribution, California Bearing Ratio (CBR), unconfined compressive strength (UCS) test, repeated load triaxial (RLT) test, flexural beam test and wheel-tracking (WT) test. The UCS, resilient modulus, permanent deformation, modulus of rupture and flexural beam fatigue properties indicated that cement stabilized triple blends containing up to 15% RG met the local road authority specification requirements. WT testing also confirmed that the rutting resistance of cement stabilized with 15% RG triple blend was well inside the limits defined by local road authorities.